My Math Forum Inequality proof

 Elementary Math Fractions, Percentages, Word Problems, Equations, Inequations, Factorization, Expansion

 November 3rd, 2017, 09:37 AM #1 Senior Member   Joined: Dec 2015 From: Earth Posts: 238 Thanks: 27 Inequality proof $\displaystyle x , y , z \in R^{+} \;$ are positive real numbers and $\displaystyle \; x+y+z=3$ prove $\displaystyle \; x^{y+z}y^{z+x}z^{x+y}\leq 1$
 November 3rd, 2017, 12:40 PM #2 Senior Member   Joined: Sep 2016 From: USA Posts: 415 Thanks: 228 Math Focus: Dynamical systems, analytic function theory, numerics Here is a rough sketch for you to fill in the details. 1. Prove that $x^{y+z}y^{x+z}z^{x+y} \leq (xyz)^3$. Hint: Use the weighted AM/GM inequality: $\left( \prod_{j=1}^n a_j^{w_j} \right)^{\frac{1}{W}} \leq \frac{1}{W} \sum_{j = 1}^{n} w_ja_j$ where $W = \sum_{j = 1}^{n} w_j$ where $a_j$ are each non-negative. 2. Let $f(x,y,z) = (xyz)^3$ and let $D = \{(x,y,z) : x + y + z =1, x,y,z \geq 0 \}$. $f$ is continuous which means $D$ is closed so $f$ attains its maximum on $D$. Note that $f = 0$ on $\partial D$ so the inequality is satisfied there. On the interior one finds maxima of $f$ satisfying $x + y + z = 1$ only if $\nabla f$ is parallel to $(1,1,1)$. This is equivalent to $xy = yz = xz$ which is only satisfied when $x = y = z = 1$ and we see that in this case $x^{y+z}y^{x+z}z^{x+y} = 1$. Hence, the inequality holds for all $(x,y,z) \in D$ and in particular, on the interior where $x + y + z = 1$ and $x,y,z$ are positive. Alternatively, another application of AM/GM gives you immediately that $(xyz)^3 \leq (\frac{x + y + z}{3})^3 = 1$ Thanks from idontknow Last edited by SDK; November 3rd, 2017 at 12:55 PM.
 November 5th, 2017, 01:16 AM #3 Senior Member   Joined: Dec 2015 From: Earth Posts: 238 Thanks: 27 I post quick method , $\displaystyle y=(3-x)lnx$ $\displaystyle y''<0 \Rightarrow y(a)+y(b)+y(c) \leq 3y(\frac{a+b+c}{3})$ $\displaystyle \ln a^{3-a} + \ln b^{3-b} +\ln c^{3-c} \leq 3y(\frac{a+b+c}{3})=1$ $\displaystyle \ln a^{3-a}b^{3-b}c^{3-c}\leq 1$ $\displaystyle a^{3-a}b^{3-b}c^{3-c}=a^{b+c}b^{c+a}c^{a+b}\leq 1$

 Tags inequality, proof

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post klim Real Analysis 0 December 20th, 2014 05:22 AM KyVanchhay Math Events 0 July 27th, 2013 01:24 AM Jakarta Number Theory 5 March 4th, 2013 04:56 AM ZardoZ Algebra 3 September 11th, 2012 02:16 PM chaolun Real Analysis 2 April 22nd, 2011 12:10 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top